Effectiveness of Implementing Productive Skills Evaluation for Students in BIPA Learning - Haryanti, Novi; Eriyanti, Ribut Wahyu; Sunaryo, Hari (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
This study aims to analyze the effectiveness of evaluation practices in developing students' productive skills in Indonesian Language Learning for Foreign Speakers (BIPA), particularly in speaking and writing. Using a mixed methods approach, data were collected through speaking and writing tests, questionnaires, semi-structured interviews, and observations. The findings show that consistent evaluation frequency and relevant learning contexts significantly influence students’ perceptions and the development of their productive skills. Performance-based evaluations—such as monologues, dialogues, and writing tasks grounded in real-life situations—were found to be the most effective and meaningful. However, feedback delivery remains a major weakness, as many students felt that the feedback they received was too vague and not helpful enough for improving their skills. Therefore, there is a need to develop an evaluation system that is not only regular and contextual but also provides practical and targeted feedback. These findings are expected to serve as a reference for designing more effective BIPA evaluation strategies, focusing on strengthening speaking and writing skills, and supporting students in becoming active users of the Indonesian language in their daily lives.